2011
DOI: 10.2203/dose-response.11-021.zhao
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of Signaling Pathways Mediating Cell Cycle Checkpoint Control and Apoptotic Responses to Ionizing Radiation-Induced DNA Damage

Abstract: Rory B. Conolly ᮀ Hamner Institutes for Health Sciences, USA and US EPA ᮀ The shape of dose response of ionizing radiation (IR) induced cancer at low dose region, either linear non-threshold or J-shaped, has been a debate for a long time. This dose response relationship can be influenced by built-in capabilities of cells that minimize the fixation of IR-mediated DNA damage as pro-carcinogenic mutations. Key capabilities include sensing of damage, activation of cell cycle checkpoint arrests that provide time ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 95 publications
2
10
0
Order By: Relevance
“…The biological mechanism leading to the J-shaped dose response was identified as saturation of the checkpoint arrest time: The induced checkpoint arrest time is longer per unit of IR dose in the low dose region than that in the high dose region. It is consistent with how toxicologists intuitively perceive bi-phasic hormetic phenomena (detailed review of previous work of model development can be found in Ricci, 2010 andZhao et al, 2012).…”
supporting
confidence: 81%
See 2 more Smart Citations
“…The biological mechanism leading to the J-shaped dose response was identified as saturation of the checkpoint arrest time: The induced checkpoint arrest time is longer per unit of IR dose in the low dose region than that in the high dose region. It is consistent with how toxicologists intuitively perceive bi-phasic hormetic phenomena (detailed review of previous work of model development can be found in Ricci, 2010 andZhao et al, 2012).…”
supporting
confidence: 81%
“…Adopting these mechanisms, we developed our first generation IRinduced cancer dose response relationship model based on systems biology approach (Zhao and Ricci, 2010;Zhao et al, 2012). The signaling I.…”
Section: The First Generation Of Ir Induced Cell Cycle Checkpoint Conmentioning
confidence: 99%
See 1 more Smart Citation
“…While cell growth is normally restrained by the control of cell cycle, cell division cycle is under the regulation of the Cdk family of serin/threonine kinase and cyclins. G2/M transition is regulated by CyclinB1/CDC2 complex in mammalian cells (13,14), and the activity of this complex is regulated by many factors. For example, dual specificity phosphatase CDC25C activates CDC2 via upholding phosphorylation on the Thr14 and Tyr15 of CDC2 (15).…”
Section: Groupmentioning
confidence: 99%
“…Cell cycle checkpoints are another defense mechanism to protect cells from DNA damage. Many anticancer agents and radiotherapy treatments regulate cancer cell growth via cell cycle arrest at G 0 /G 1 , S, or G 2 /M phases, and then induce apoptotic cell death [46][47][48][49] . Previous studies have indicated that various anticancer drugs and radiotherapy treatments induce cell cycle arrest at the G 2 /M phase [50,51] .…”
Section: Discussionmentioning
confidence: 99%